CsPbBr3 perovskite quantum dot germanium borate glass material as well as preparation method and application thereof

By embedding perovskite quantum dots into germanium borate glass and introducing LiF, the problem of poor environmental stability of perovskite quantum dot materials is solved, and its excellent performance and stability in optoelectronic devices are achieved, and the application prospects are expanded. .

CN119285236AActive Publication Date: 2025-01-10CHINA JILIANG UNIV
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411383902.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2025-01-10
Estimated Expiration
2044-09-30

AI Technical Summary

Technical Problem

The existing perovskite quantum dot materials are susceptible to environmental factors such as humidity, heat and oxygen, and have poor environmental stability, which limits their use in practical applications.

Method used

By embedding perovskite quantum dots into germanium borate glass with low phonon energy, high rare earth ion solubility and good optical transmission performance, and introducing LiF, CsPbBr3 perovskite quantum dots germanium boric acid was prepared by traditional melt quenching method. Salt glass material improves its environmental stability and luminous properties.

Benefits of technology

The environmental stability and luminous performance of perovskite quantum dots have been significantly improved, and their application prospects have been expanded in optoelectronic devices. The preparation method is simple to operate, low cost, and suitable for industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119285236A_ABST
    Figure CN119285236A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of solid luminescent materials, in particular to a CsPbBr3 perovskite quantum dot germanium borate glass material and a preparation method and application thereof. The CsPbBr3 perovskite quantum dot germanium borate glass material provided by the invention is prepared from the following chemical components in parts by mass: 25 to 29 parts of GeO2, 100 to 108 parts of H3BO3, 2 to 6 parts of ZnO, 1 to 4 parts of SrCO3, 3 to 8 parts of Cs2CO3, 2 to 7 parts of PbO and 1 to 8 parts of NaBr. The perovskite quantum dots are embedded into the germanium borate glass, so that the environmental stability of the perovskite quantum dots is improved, and the application prospect of the perovskite quantum dots in photoelectric devices is expanded. Furthermore, LiF is introduced into the perovskite quantum dot germanium borate glass material, so that not only is the fluorescence quantum yield of the perovskite quantum dot glass improved, but also the environmental stability of the perovskite quantum dots can be further improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of solid luminescent materials, and in particular to a CsPbBr 3 Perovskite quantum dot germanium borate glass material and its preparation method and application. Background Art

[0002] Perovskite quantum dots refer to perovskite crystal structures (with the structural formula ABX 3 These nanoparticles exhibit quantum confinement effects, that is, their optical and electrical properties are affected by their size and shape. Perovskite quantum dot materials have attracted extensive attention in optoelectronic devices, light-emitting diodes (LEDs), photovoltaic cells, and optical sensors due to their excellent optoelectronic properties (such as high optical absorption coefficient, narrow emission spectrum line width, high fluorescence quantum yield, and adjustable spectral range). However, existing perovskite quantum dot materials are easily affected by environmental factors such as humidity, heat, and oxygen, and have poor environmental stability, which seriously limits their application in practice. Summary of the invention

[0003] In view of this, the object of the present invention is to provide a CsPbBr 3 Perovskite quantum dot germanium borate glass material and its preparation method and application. The CsPbBr 3 Perovskite quantum dots in germanium borate glass materials have good environmental stability.

[0004] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0005] The present invention provides a CsPbBr 3 Perovskite quantum dot germanium borate glass material, in terms of the amount of substance, the chemical composition includes: GeO 2 25~29 parts, H 3 BO 3 100-108 parts, ZnO 2-6 parts, SrCO 3 1~4 parts, Cs 2 CO 3 3 to 8 parts, PbO 2 to 7 parts and NaBr 1 to 8 parts.

[0006] Preferably, the GeO 2 Based on the amount of substance, the CsPbBr 3 The chemical composition of the perovskite quantum dot germanium borate glass material also includes 0 to 4 parts of LiF, and the amount of LiF is not zero.

[0007] Preferably, based on the amount of substance, the CsPbBr 3The chemical composition of perovskite quantum dot germanium borate glass materials includes GeO 2 25~29 parts, H 3 BO 3 100-108 parts, ZnO 4 parts, SrCO 3 2 copies, Cs 2 CO 3 6 parts, PbO 4 parts, NaBr 5 parts and LiF 0-4 parts.

[0008] The present invention provides the CsPbBr 3 The preparation method of the perovskite quantum dot germanium borate glass material comprises the following steps:

[0009] According to the CsPbBr 3 The chemical composition of the perovskite quantum dot germanium borate glass material is obtained by mixing the raw materials and then melting them to obtain a glass melt;

[0010] The glass melt is cast and then annealed to obtain the CsPbBr 3 Perovskite quantum dot germanium borate glass material;

[0011] Preferably, the melting temperature is 950-1050° C. and the melting time is 10-30 min.

[0012] Preferably, the annealing temperature is 300-400° C. and the time is 2-4 hours.

[0013] Preferably, the casting time is less than 6 minutes.

[0014] Preferably, the casting molding comprises: pouring the glass melt onto a preheated preheating plate and letting it stand.

[0015] Preferably, the temperature of the preheated preheating plate is 300-450° C.; and the pouring time is less than 1 min.

[0016] The present invention provides the CsPbBr 3 Perovskite quantum dot germanium borate glass material or CsPbBr prepared by the preparation method described in the above technical scheme 3 Application of perovskite quantum dot germanium borate glass materials in optoelectronic devices or photovoltaic cells.

[0017] The present invention provides a CsPbBr 3 Perovskite quantum dot germanium borate glass material, in terms of the amount of substance, the chemical composition includes: GeO 2 25~29 parts, H 3 BO 3100-108 parts, ZnO 2-6 parts, SrCO 3 1~4 parts, Cs 2 CO 3 3 to 8 parts, PbO 2 to 7 parts and NaBr 1 to 8 parts. The present invention improves the environmental stability of perovskite quantum dots and expands their application prospects in optoelectronic devices by embedding perovskite quantum dots into germanium borate glass with low phonon energy, high rare earth ion solubility and good optical transmission performance.

[0018] Furthermore, the present invention is carried out by 3 The introduction of LiF (lithium fluoride) into perovskite quantum dot germanium borate glass material not only improves the luminescence performance of perovskite quantum dots and the fluorescence quantum yield of perovskite quantum dot glass, but also can further improve the environmental stability of perovskite quantum dots.

[0019] The CsPbBr 3 Preparation method of perovskite quantum dot germanium borate glass material Germanium borate glass was prepared by traditional melt quenching method, and CsPbBr was successfully prepared in germanium borate glass by self-crystallization method. 3 Perovskite quantum dots have excellent environmental stability; moreover, the preparation method provided by the present invention is simple to operate, low in cost, has little environmental pollution, and is suitable for industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 CsPbBr prepared in Examples 1 to 5 3 (a) Emission spectrum of perovskite quantum dot germanium borate glass material and (b) fluorescence quantum dot yield spectrum;

[0021] Figure 2 CsPbBr prepared in Examples 1 to 5 3 (a) XRD diffraction pattern and (b) high-resolution transmission electron microscopy image of perovskite quantum dot germanium borate glass material;

[0022] Figure 3 CsPbBr prepared in Examples 1 to 5 3 (a) Raman spectrum and (b) Fourier transform infrared spectrum of perovskite quantum dot germanium borate glass material;

[0023] Figure 4 CsPbBr prepared in Examples 1 to 5 3 The luminescence results of perovskite quantum dot germanium borate glass material immersed in water for 1 to 30 days;

[0024] Figure 5 This is a photoluminescence intensity graph of PG2 prepared in Example 3 after being immersed in water for 1 to 30 days;

[0025] Figure 6 The stability test results of the conventional colloidal perovskite quantum dots prepared in Comparative Example 1 after being immersed in water for 30 days;

[0026] Figure 7 is a photoluminescence intensity diagram of PG2 prepared in Example 3 in the temperature range of 300 to 420K;

[0027] Figure 8 This is a photoluminescence intensity graph of the PG2 sample prepared in Example 3, which was continuously irradiated under a 365 nm ultraviolet lamp for 30 days. DETAILED DESCRIPTION

[0028] The present invention provides a CsPbBr 3 Perovskite quantum dot germanium borate glass material, in terms of the amount of substance, the chemical composition includes: GeO 2 25~29 parts, H 3 BO 3 100-108 parts, ZnO 2-6 parts, SrCO 3 1~4 parts, Cs 2 CO 3 3 to 8 parts, PbO 2 to 7 parts and NaBr 1 to 8 parts.

[0029] In terms of the amount of substance, the CsPbBr 3 The chemical composition of perovskite quantum dot germanium borate glass materials includes GeO 2 25 to 29 parts, in a specific embodiment, the GeO 2 The amount of the substance can be 25 parts, 26 parts, 27 parts, 28 parts or 29 parts.

[0030] The GeO 2 The CsPbBr provided by the present invention is based on the amount of the substance. 3 The chemical composition of perovskite quantum dot germanium borate glass material includes H 3 BO 3 100 to 108 parts, in a specific embodiment, the H 3 BO 3 The amount of the substance can be 100 parts, 101 parts, 102 parts, 103 parts, 104 parts, 105 parts, 106 parts, 107 parts or 108 parts.

[0031] The GeO 2 The CsPbBr provided by the present invention is based on the amount of the substance. 3The chemical composition of the perovskite quantum dot germanium borate glass material includes 2 to 6 parts of ZnO. In a specific embodiment, the amount of ZnO can be 2 parts, 3 parts, 4 parts, 5 parts or 6 parts.

[0032] The GeO 2 The CsPbBr provided by the present invention is based on the amount of the substance. 3 The chemical composition of the perovskite quantum dot germanium borate glass material includes SrCO 3 1 to 4 parts, in a specific embodiment, the SrCO 3 The amount of the substance can be 1 part, 2 parts, 3 parts or 4 parts.

[0033] The GeO 2 The CsPbBr provided by the present invention is based on the amount of the substance. 3 The chemical composition of perovskite quantum dot germanium borate glass materials includes Cs 2 CO 3 3 to 8 parts, in a specific embodiment, the Cs 2 CO 3 The amount of the substance can be 3 parts, 4 parts, 5 parts, 6 parts, 7 parts or 8 parts.

[0034] The GeO 2 The CsPbBr provided by the present invention is based on the amount of the substance. 3 The chemical composition of the perovskite quantum dot germanium borate glass material includes 2 to 7 parts of PbO. In a specific embodiment, the amount of PbO can be 2 parts, 3 parts, 4 parts, 5 parts, 6 parts or 7 parts.

[0035] The GeO 2 The CsPbBr provided by the present invention is based on the amount of the substance. 3 The chemical composition of the perovskite quantum dot germanium borate glass material includes 1 to 8 parts of NaBr. In a specific embodiment, the amount of NaBr can be 1 part, 2 parts, 3 parts, 4 parts, 5 parts, 6 parts, 7 parts or 8 parts.

[0036] The GeO 2 The CsPbBr provided by the present invention is based on the amount of the substance. 3 The chemical composition of the perovskite quantum dot germanium borate glass material may also include 0 to 4 parts of LiF, and the amount of LiF is not 0. In a specific embodiment, the amount of LiF may be 1 part, 2 parts, 3 parts or 4 parts.

[0037] In the present invention, the CsPbBr 3The chemical composition of perovskite quantum dot germanium borate glass materials can include GeO 2 25~29 parts, H 3 BO 3 100-108 parts, ZnO 4 parts, SrCO 3 2 copies, Cs 2 CO 3 6 parts, PbO 4 parts, NaBr 5 parts and LiF 0-4 parts.

[0038] The present invention provides the CsPbBr 3 The preparation method of the perovskite quantum dot germanium borate glass material comprises the following steps:

[0039] According to the CsPbBr 3 The chemical composition of the perovskite quantum dot germanium borate glass material is obtained by mixing the raw materials and then melting them to obtain a glass melt;

[0040] The glass melt is cast and then annealed to obtain the CsPbBr 3 Perovskite quantum dot germanium borate glass materials.

[0041] Unless otherwise specified, the materials and equipment used in the present invention are all commercially available products in the art.

[0042] The present invention is based on the CsPbBr 3 The chemical composition of the perovskite quantum dot germanium borate glass material is obtained by mixing the raw materials and melting them to obtain a glass melt. In the present invention, the amount of the optional substances in the raw materials can be the same as that of the prepared CsPbBr 3 The chemical composition of the perovskite quantum dot germanium borate glass material has the same amount of substances, which will not be repeated here.

[0043] In the present invention, the melting temperature may be 950-1050°C. In a specific embodiment, the melting temperature may be 950°C, 980°C, 1000°C, 1020°C or 1050°C. The melting time may be 10-30 minutes. In a specific embodiment, the melting time may be 10 minutes, 15 minutes, 20 minutes, 25 minutes or 30 minutes. In a specific embodiment, the mixing may include grinding and mixing. The present invention has no special restrictions on the grinding and mixing time and the particle size of the mixture obtained by grinding and mixing, as long as the raw materials can be completely mixed. In the present invention, the particle size of the mixture obtained by grinding and mixing may be 1-5 μm. In a specific embodiment, it may be 1 μm, 2 μm, 3 μm, 4 μm or 5 μm.

[0044] The present invention can place the mixed material obtained by mixing in a crucible, and place the crucible in a muffle furnace for melting. In a specific embodiment, the crucible can be an alumina crucible; and the muffle furnace can be a silicon carbide muffle furnace.

[0045] After obtaining the glass melt, the present invention casts the glass melt and then anneals it to obtain the CsPbBr 3 Perovskite quantum dot germanium borate glass materials.

[0046] In the present invention, the casting time may be less than 6 min. In a specific embodiment, the casting time may be 5.2 min, 5.3 min, 5.4 min, 5.5 min, 5.6 min, 5.7 min or 5.8 min.

[0047] In a specific embodiment, the casting molding may include: pouring the glass melt onto a preheated preheating plate and letting it stand. In the present invention, the temperature of the preheated preheating plate may be 300-450°C. In a specific embodiment, the temperature of the preheated preheating plate may be 300°C, 320°C, 350°C, 370°C, 400°C or 450°C; the casting time may be <1min. The present invention pours the glass melt onto the preheated preheating plate quickly (<1min) to prevent the glass melt from cooling and solidifying due to a slow casting speed and being unable to be poured out.

[0048] In a specific embodiment, the temperature of the static state can be the same as the temperature of the preheating plate after preheating, which will not be described in detail. The present invention allows the preheating plate to be static after pouring to prevent the glass melt from breaking due to a rapid drop in temperature.

[0049] In the present invention, the annealing temperature may be 300-400°C, and in a specific embodiment, the annealing temperature may be 300°C, 320°C, 350°C, 370°C or 400°C; the annealing time may be 2-4h, and in a specific embodiment, the annealing time may be 2h, 2.5h, 3h, 3.5h or 4h. In a specific embodiment, the annealing may be performed in an annealing furnace.

[0050] After the annealing is completed, the present invention may further include cooling the obtained annealed glass to room temperature to obtain the CsPbBr 3 Perovskite quantum dot germanium borate glass material. In a specific embodiment, the cooling may include cooling with an annealing furnace. The present invention cools the annealed glass obtained by annealing to room temperature with the furnace, eliminates the internal stress of the glass, and improves the obtained CsPbBr 3 Environmental stability of perovskite quantum dot germanium borate glass materials.

[0051] The present invention provides the CsPbBr 3 Perovskite quantum dot germanium borate glass material or CsPbBr prepared by the preparation method described in the above technical scheme 3 Application of perovskite quantum dot germanium borate glass material in optoelectronic devices or photovoltaic cells. In a specific embodiment, the optoelectronic device can be a light emitting diode. The CsPbBr 3 Perovskite quantum dot germanium borate glass material has good environmental stability. When used in optoelectronic devices or photovoltaic cells, it can maintain strong luminescence in different environments.

[0052] In order to further illustrate the present invention, the following is a CsPbBr 3 The perovskite quantum dot germanium borate glass material and its preparation method and application are described in detail, but they should not be understood as limiting the scope of protection of the present invention.

[0053] Example 1

[0054] In terms of the amount of substance, GeO 2 27 copies, H 3 BO 3 104 parts, ZnO 4 parts, SrCO 3 2 copies, Cs 2 CO 3 The prepared raw materials of 6 parts of Ag, 4 parts of PbO and 5 parts of NaBr were ground and mixed to a particle size of about 2 μm, loaded into an alumina crucible, placed in a muffle furnace, and melted at 1000° C. for 20 minutes to obtain a glass melt.

[0055] The obtained glass melt was poured onto a preheated plate preheated to 400°C within 1 min, left to stand for 5 min, then transferred to an annealing furnace and annealed at 350°C for 3 h. The annealing furnace was cooled to room temperature to obtain CsPbBr 3 Perovskite quantum dot germanium borate glass material (denoted as PG0).

[0056] Example 2

[0057] CsPbBr was prepared according to the preparation method in Example 1. 3 The perovskite quantum dot germanium borate glass material (denoted as PG1) is different from Example 1 only in that, in terms of the amount of substance, the raw materials for preparation are: GeO 2 27 copies, H 3 BO 3 104 parts, ZnO 4 parts, SrCO 3 2 copies, Cs 2 CO 36 parts, PbO 4 parts, NaBr 5 parts and LiF 1 part.

[0058] Example 3

[0059] CsPbBr was prepared according to the preparation method in Example 1. 3 The perovskite quantum dot germanium borate glass material (denoted as PG2) is different from Example 1 only in that, in terms of the amount of substance, the raw materials for preparation are: GeO 2 27 copies, H 3 BO 3 104 parts, ZnO 4 parts, SrCO 3 2 copies, Cs 2 CO 3 6 parts, PbO 4 parts, NaBr 5 parts and LiF 2 parts.

[0060] Example 4

[0061] CsPbBr was prepared according to the preparation method in Example 1. 3 The perovskite quantum dot germanium borate glass material (denoted as PG3) is different from Example 1 only in that, in terms of the amount of substance, the raw materials for preparation are: GeO 2 27 copies, H 3 BO 3 104 parts, ZnO 4 parts, SrCO 3 2 copies, Cs 2 CO 3 6 parts, PbO 4 parts, NaBr 5 parts and LiF 3 parts.

[0062] Example 5

[0063] CsPbBr was prepared according to the preparation method in Example 1. 3 The perovskite quantum dot germanium borate glass material (denoted as PG4) is different from Example 1 only in that, in terms of the amount of substance, the raw materials for preparation are: GeO 2 27 copies, H 3 BO 3 104 parts, ZnO 4 parts, SrCO 3 2 copies, Cs 2 CO 3 6 parts, PbO 4 parts, NaBr 5 parts and LiF 4 parts.

[0064] Comparative Example 1

[0065] Literature (Daqin Chen, Shuo Yuan, Jiangkun Chen, et al. Robust CsPbX 3(X=Cl, Br, and I)perovskite quantum dot embedded glasses: nanocrystallization, improved stability and visible full-spectral tunable. [J] Journal of Materials Chemistry C, 2018, 6, 12864) prepared traditional colloidal perovskite quantum dots.

[0066] Figure 1 CsPbBr prepared in Examples 1 to 5 3 (a) Emission spectrum of perovskite quantum dot germanium borate glass material and (b) fluorescence quantum dot yield spectrum. Figure 1 As shown in (a), LiF doping can improve the 3 The photoluminescence intensity of perovskite quantum dot germanium borate glass material, when the LiF doping concentration is 2 mol%, CsPbBr 3 The photoluminescence intensity of perovskite quantum dots reaches the highest level. Further increasing the LiF doping concentration will reduce the CsPbBr 3 The photoluminescence intensity of perovskite quantum dots (may be caused by concentration quenching). Figure 1 As shown in (b), LiF doping can 3 The fluorescence quantum yield of the photoluminescence intensity of the perovskite quantum dot germanium borate glass material was increased from 10.5% to 49.3%.

[0067] Figure 2 CsPbBr prepared in Examples 1 to 5 3 (a) XRD diffraction pattern and (b) high-resolution transmission electron microscopy image of perovskite quantum dot germanium borate glass material. Figure 2 As shown in (a), since self-crystallized glass cannot provide high-energy heat, CsPbBr 3 The perovskite quantum dots are small in size, so the corresponding CsPbBr 3 XRD diffraction peaks of perovskite quantum dots, but Figure 2 The black spheres can be observed by high-resolution transmission electron microscopy in (b), and the interplanar spacing is calculated to be Corresponding to CsPbBr 3 The (223) crystal plane of the perovskite quantum dots shows that the prepared CsPbBr 3 CsPbBr was precipitated from perovskite quantum dot germanium borate glass material 3 Perovskite quantum dots.

[0068] Figure 3CsPbBr prepared in Examples 1 to 5 3 (a) Raman spectrum and (b) Fourier infrared spectrum of perovskite quantum dot germanium borate glass material. Figure 3 It can be seen that with the increase of LiF doping concentration, the symmetric stretching vibration band corresponding to the BOB bond and the bending vibration intensity of the boron-oxygen ring increase. This is because part of [BO 4] Tetrahedral [BO 3 ] triangle transformation, resulting in the network structure of the glass material changing from a three-dimensional framework structure to a two-dimensional layered structure, which also makes the glass material looser, promoting the migration of cesium ions, lead ions and bromide ions, and then promoting CsPbBr 3 Production of perovskite quantum dots.

[0069] Figure 4 CsPbBr prepared in Examples 1 to 5 3 The luminescence results of perovskite quantum dot germanium borate glass material immersed in water for 1 to 30 days. Figure 4 It can be seen that after immersion in water for 30 days, CsPbBr 3 Perovskite quantum dot germanium borate glass material still has strong luminescence, indicating that the prepared CsPbBr 3 Perovskite quantum dot germanium borate glass material has excellent water stability.

[0070] Take PG2 as an example. Figure 5 The photoluminescence intensity of PG2 prepared in Example 3 is shown after being immersed in water for 1 to 30 days. Figure 5 It can be seen that after immersion in water for 30 days, the photoluminescence intensity of the PG2 sample remained at 79.7% of the initial value, indicating that the CsPbBr prepared by the present invention 3 Perovskite quantum dot glass materials have good water stability.

[0071] Figure 6 The stability test results of the conventional colloidal perovskite quantum dots prepared in Comparative Example 1 after being immersed in water for 30 days are shown in FIG. Figure 6 It can be seen that the CsPbBr prepared by the present invention 3 The perovskite quantum dot glass material still has strong luminescence after being immersed in water for 30 days, while the traditional colloidal perovskite quantum dots prepared in Comparative Example 1 lose luminescence after being immersed in water for several hours.

[0072] Figure 7 The photoluminescence intensity diagram of PG2 prepared in Example 3 in the temperature range of 300 to 420K. Figure 7It can be seen that the luminescence intensity of PG2 decreases during the heating process, which is attributed to the increase in the probability of non-radiative transition as the temperature rises. When the temperature gradually decreases to 300K, the luminescence intensity of PG2 remains above 80% of that before the heating, indicating that the CsPbBr prepared by the present invention 3 Perovskite quantum dot glass material has good temperature resilience (thermal stability).

[0073] Figure 8 This is the photoluminescence intensity diagram of the PG2 sample prepared in Example 3, which was continuously irradiated under a 365 nm ultraviolet lamp for 30 days. Figure 8 It can be seen that after continuous irradiation under ultraviolet light for 30 days, the photoluminescence intensity of PG2 is 85.9% of the original value, indicating that the CsPbBr prepared by the present invention 3 Perovskite quantum dot glass material has good photostability.

[0074] In summary, the CsPbBr 3 Perovskite quantum dot germanium borate glass materials have excellent water stability, light stability, thermal stability, and excellent environmental stability. Moreover, through LiF doping and self-crystallization, CsPbBr with high luminescence intensity and high water stability can be prepared in germanium borate glass. 3 Perovskite quantum dot glass material.

[0075] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A CsPbBr3 perovskite quantum dot germanium borate glass material, the chemical composition of which, in terms of molar fraction, comprises: GeO2 25-29 parts, H3BO3 100-108 parts, ZnO 2-6 parts, SrCO3 1-4 parts, Cs2CO3 3-8 parts, PbO 2-7 parts and NaBr 1-8 parts.

2. The CsPbBr3 perovskite quantum dot germanium borate glass material according to claim 1, characterized in that: Based on the amount of GeO2, the chemical composition of the CsPbBr3 perovskite quantum dot germanium borate glass material also includes 0 to 4 parts of LiF, and the amount of LiF is not 0.

3. The CsPbBr3 perovskite quantum dot germanium borate glass material according to claim 1 or 2, characterized in that: Calculated by the amount of substances, the chemical composition of the CsPbBr3 perovskite quantum dot germanium borate glass material includes 25-29 parts of GeO2, 100-108 parts of H3BO3, 4 parts of ZnO, 2 parts of SrCO3, 6 parts of Cs2CO3, 4 parts of PbO, 5 parts of NaBr and 0-4 parts of LiF.

4. The method for preparing the CsPbBr3 perovskite quantum dot germanium borate glass material according to any one of claims 1 to 3, characterized in that: The following steps are involved: According to the chemical composition of the CsPbBr3 perovskite quantum dot germanium borate glass material, the prepared raw materials are mixed and then melted to obtain a glass melt; The glass melt is cast and then annealed to obtain the CsPbBr3 perovskite quantum dot germanium borate glass material.

5. The preparation method according to claim 4, characterized in that: The melting temperature is 950-1050° C. and the melting time is 10-30 minutes.

6. The preparation method according to claim 4, characterized in that: The annealing temperature is 300-400° C. and the annealing time is 2-4 hours.

7. The preparation method according to claim 4, characterized in that: The pouring molding time is less than 6 minutes.

8. The preparation method according to claim 4 or 7, characterized in that: The casting molding comprises: casting the glass melt onto a preheated preheating plate and letting it stand.

9. The preparation method according to claim 8, characterized in that: The temperature of the preheated preheating plate is 300-450° C.; the pouring time is less than 1 minute.

10. Use of the CsPbBr3 perovskite quantum dot germanium borate glass material according to any one of claims 1 to 3 or the CsPbBr3 perovskite quantum dot germanium borate glass material prepared by the preparation method according to any one of claims 4 to 9 in optoelectronic devices or photovoltaic cells.

Citation Information

Patent Citations

  • CsPbBr3 (cesium-lead-bromide) perovskite quantum dot fluorescent glass for display of wide color gamut and preparation method and application thereof

    CN110294597A

  • Sr&lt;2+&gt; doped CsPbBr3 quantum dot germanium borosilicate glass as well as preparation method and application thereof

    CN111517657A

  • Preparation method and application of efficient all-inorganic perovskite quantum dot glass

    CN112047635A

  • Full-inorganic perovskite quantum dot fluorescent glass as well as preparation method and application thereof

    CN113912291A

  • Full-inorganic perovskite quantum dot microcrystalline glass material and preparation method thereof

    CN115124247A